Tiny grains shining bright in the gaps of Herbig Ae transitional discs. Issue 3 (17th April 2019) - Birchall, Eloise K; Ireland, Michael J; Federrath, Christoph; Monnier, John D; Kraus, Stefan; Willson, Matthew; Kraus, Adam L; Rizzuto, Aaron; Agnew, Matthew T; Maddison, Sarah T
ABSTRACT: This work presents a study of two Herbig Ae transitional discs, Oph IRS 48 and HD 169142; which both have reported rings in their dust density distributions. We use Keck-II/NIRC2 adaptive optics imaging observations in the L′ filter (3.8 $μ$ m) to probe the regions of these discs inwards of${\sim }20\, au$ from the star. We introduce our method for investigating these transitional discs, which takes a forward modelling approach: making a model of the disc (using the Monte Carlo radiative transfer coderadmc3d ), convolving it with point spread functions of calibrator stars, and comparing the convolved models with the observational data. The disc surface density parameters are explored with a Monte Carlo Markov Chain technique. Our analysis recovers emission from both of the discs interior to the well-known optically thick walls, modelled as a ring of emission at${\sim }15\, au$ in Oph IRS 48, and${\sim }7\, au$ for HD 169142, and identifies asymmetries in both discs. Given the brightness of the near-symmetric rings compared to the reported companion candidates, we suggest that the reported companion candidates can be interpreted as slightly asymmetric disc emission or illumination.